Tracking the Lithium and Strontium Isotope Signature of Hydrothermal Plume in the Water Column: A Case Study at the EMSO-Azores Deep-Sea Observatory - Artigue, Lise; Chavagnac, Valérie; Destrigneville, Christine; Ferron, Bruno; Cathalot, Cécile (Frontiers in Environmental Chemistry, 2022)
Lithium (Li) and strontium (Sr) are two economically relevant chemical elements whose oceanic biogeochemical cycles are not fully constrained. Particularly, how they disperse and behave from hydrothermal sources into the water column is understudied while hydrothermal systems on the global mid-ocean ridge network (~67000 km) represent one of the main sources of Li. This study aims to provide new insights on the dissolved Li (DLi) and Sr (DSr) behavior in the water column. Here, we present for the first time DLi and DSr elemental and isotopic (∂7Li, and 87Sr/86Sr) profiles from six casts distributed over the Lucky Strike hydrothermal vent field (LSHF, Mid-Atlantic Ridge). DLi and DSr results reflect a hydrothermal contribution to the water column up to ~300 m above the seafloor which can be quantified by up to 10% based on the dLi dataset. For increasing hydrothermal contribution ∂7Li values of the water column become heavier most likely due to mineral–seawater interactions i.e. manganese oxide formed during the mixing of hydrothermal fluid and seawater. Contrarily to DLi, DSr, and ∂7Li datasets, the hydrothermal contribution to the water column is not evidenced by the 87Sr/86Sr ratios which fall within the range of oligotrophic oceanic waters. Surprisingly, some geographically distant casts display at the same depth identical DLi and DSr concentrations or similar ∂7Li signatures. We attribute these features to the current dynamics above the LSHF, suggesting that the hydrothermal signature of the western casts can overprint those of the eastern and center casts in less than one hour at the LSHF km-scale. Overall, this study highlights that (i) as for many elements, DLi, DSr, and ∂7Li can be used to track the hydrothermal signature to the water column at a km-scale while 87Sr/86Sr cannot, (ii) local currents play a major role in advecting the hydrothermal contribution away from the hydrothermal sources, and (iii) mineral–seawater interaction processes are at play during the mixing between hydrothermal fluid and seawater and impact the ∂7Li hydrothermal signature. Our study suggests that chemical tracers of hydrothermal input have to be chosen depending on the spatial scale of the studied area.